AGEISM IN THE WORKPLACE AND POTENTIAL LEGAL PROTECTION IN INDONESIA - Candra, Fransisca Fitriana Riani; Yulianita, Rosalinda Chandra (Faculty of Law Atma Jaya Yogyakarta University, 2024)
This research will focus on ageism or age discrimination in in the workplace setting. In Indonesia, there has not yet been specific attention given to combat age discrimination, one of which is proven by the considerations of judges in Constitutional Court Decision Number 35/PUU-XXII/2024. Regulations in Indonesia, as well as their implementation, also do not sufficiently promote equal treatment regardless of age. Therefore, this research will analyze the urgency, challenges, and propose potential legal protection to promote anti ageism in Indonesia by comparing anti-age discrimination regulations in other countries and examining rulings related to age discrimination. This research employs normative legal research with comparative approaches. Ultimately, the findings aim to inform policymakers and stakeholders about the importance of addressing ageism and fostering an inclusive workplace.